OPTIMASI BIAYA PENGIRIMAN TELUR AYAM MENGGUNAKAN PENDEKATAN MODEL TRANSPORTASI NWC DAN SOFTWARE LINGO - Dandi Nurdiansyah; Diva Maulana; Artia Tresnadi; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2021)
Distribution of goods from producers to the hands of consumers becomes one aspect in running a business that must be planned and taken into account in order to meet the needs of the market. Delivery of goods results in costs incurred and is one of the obstacles that are often faced. Problems in the distribution of goods include the amount of inventory, the amount of consumer demand, the distance traveled and the costs that come out during the delivery process. This study describes taking into account optimal postage with transportation methods to generate maximum efficiency costs. The problem faced in this case using the North West Corner (NWC) method, then the results of the data obtained were tested optimized using LINGO software. Before the research was conducted, the cost of postage incurred by the company is Rp.278.000. The results of the research obtained after applying the NWC is Rp.255.000 and LINGO software method is Rp.240.000. The purpose of this research is to get optimal costs on the distribution of chicken eggs to increase cost savings at Ayam Sehat.com Shop in Cimahi. Using the NWC method in this case can result in smaller distribution costs than before, then this NWC method can be applied to the Ayam Sehat.com shop